Pertanggungjawaban Pidana Hacktivist dalam Perspektif Hukum Pidana di Indonesia - Maharani, Puan; Hafrida, Hafrida; Rapik, Mohamad (PAMPAS: Journal of Criminal Law, 2024)
This article aims to analyze the criminal liability of hacktivists in Indonesia. In an increasingly advanced digital era, hacktivism has become a significant phenomenon in cyberspace. Hacktivists are individuals or groups who use hacking techniques to voice socio-political ambitions or convey ideological messages related to issues that occur in society. Specifically, this article concerns how the criminal liability of hacktivists in Indonesia and how the legal policy of criminal liability by hacktivists in Indonesia in the future. As normative juridical research, this article refers to the applicable laws and regulations. The results of this study indicate that hacktivists criminal liability in Indonesia experiences several obstacles, including the absence of specific regulation of hacktivism in legislation and obstacles in law enforcement that affect criminal liability by hacktivists. Therefore, it is necessary to reform the criminal law into legislation so that hacktivism can be specifically sanctioned as well as more effective cybercrime countermeasures. In addition, close cooperation between authorities and law enforcement agencies is needed to improve the ability to deal with cyber attacks and ensure effective criminal liability for hacktivists. Abstrak Artikel ini bertujuan untuk menganalisis pertanggungjawaban pidana hacktivist di Indonesia. Dalam era digital yang semakin maju, hacktivisme telah menjadi fenomena yang signifikan di dunia maya. Pelaku yang melakukan hacktivisme disebut hacktivist, ialah individu atau kelompok yang menggunakan teknik peretasan untuk menyuarakan ambisi sosial politik atau menyampaikan pesan ideologi terkait isu-isu yang terjadi di masyarakat. Secara khusus, artikel ini mempermasalahkan bagaimana pertanggungjawaban pidana hacktivist di Indonesia dan bagaimana kebijakan hukum dari pertanggungjawaban pidana hacktivist di Indonesia ke depannya. Sebagai penelitian yuridis normatif, artikel ini mengacu pada peraturan perundang-undangan yang berlaku. Hasil penelitian ini menunjukkan bahwa pertanggungjawaban pidana hacktivist di Indonesia mengalami beberapa hambatan, antara lain tidak diaturnya hacktivisme secara khusus dalam peraturan perundang-undangan dan hambatan dalam penegakan hukum yang mempengaruhi pertanggungjawaban pidana oleh hacktivist. Oleh karena itu, diperlukan pembaharuan hukum pidana terhadap peraturan perundang-undangan agar hacktivisme dapat dikenakan sanksi secara khusus serta upaya penanggulangan cybercrime yang lebih efektif. Selain itu, diperlukan kerjasama yang erat antara pihak berwenang dan lembaga penegak hukum untuk meningkatkan kemampuan dalam menangani serangan siber dan memastikan pertanggungjawaban pidana yang efektif terhadap hacktivist.